A New Dyslexia Reading Method and Visual Correction Position Method. (4th October 2017) - Manilla, George T.; de Braga, Joe
Pediatricians and educators may interact daily with several dyslexic patients or students. One dyslexic author accidently developed a personal, effective, corrective reading method. Its effectiveness was evaluated in 3 schools. One school utilized 8 demonstration special education students. Over 3 months, one student grew one third year, 3 grew 1 year, and 4 grew 2 years. In another school, 6 sixth-, seventh-, and eighth-grade classroom teachers followed 45 treated dyslexic students. They all excelled and progressed beyond their classroom peers in 4 months. Using cyclovergence upper gaze, dyslexic reading problems disappeared at one of the Positional Reading Arc positions of 30°, 60°, 90°, 120°, or 150° for 10 dyslexics. Positional Reading Arc on 112 students of the second through eighth grades showed words read per minute, reading errors, and comprehension improved. Dyslexia was visually corrected by use of a new reading method and Positional Reading Arc positions.